m7G regulator-mediated methylation modification patterns define immune cell infiltration and patient survival - Wang, Lu; Hu, Xing; Liu, Xiaoni; Feng, Yingmei; Zhang, Yuan; Han, Jing; Liu, Xuqing; Meng, Fankun (Frontiers in Immunology, 2022)
Numerous studies have demonstrated the important roles of epigenetic modifications in tumorigenesis, progression and prognosis. However, in hepatocellular carcinoma, the potential link between N7-methylguanosine (m7G) modification and molecular heterogeneity and tumor microenvironment (TME) remains unclear. Method: We performed a comprehensive evaluation of m7G modification patterns in 816 hepatocellular carcinoma samples based on 24 m7G regulatory factors, identified different m7G modification patterns, and made a systematic correlation of these modification patterns with the infiltration characteristics of immunocytes. Then, we built and validated a scoring tool called m7G score. Results: In this study, we revealed the presence of three distinct m7G modification patterns in liver cancer, with remarkable differences in the immunocyte infiltration characteristics of these three subtypes. The m7G scoring system of this study could assess m7G modification patterns in individual hepatocellular carcinoma patients, could predict TME infiltration characteristics, genetic variants and patient prognosis. We also found that the m7G scoring system may be useful in guiding patients' clinical use of medications. Conclusions: This study revealed that m7G methylation modifications exerted a significant role in formation of TME in hepatocellular carcinoma. Assessing the m7G modification patterns of single patients would help enhance our perception of TME infiltration characteristics and give significant insights into immunotherapy efficacy.